Lung-protective ventilation vs conventional ventilation in emergency surgery. (2nd March 2021) - Briggs, Christopher; Melia, David
Abstract : Lung-protective ventilation significantly reduces mortality in patients with acute respiratory distress syndrome, but do the advantages of this approach transfer from the intensive care unit to the operating room?